2014
DOI: 10.1177/1352458514546786
|View full text |Cite
|
Sign up to set email alerts
|

Similar biological effect of high-dose oral versus intravenous methylprednisolone in multiple sclerosis relapses

Abstract: clinicaltrials.gov identifier: NCT00753792.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Among the remaining articles, 58 articles were excluded based on titles and abstracts, as the participants and interventions in these studies were irrelevant to the aim of this meta-analysis. Finally, the remaining 9 studies were potentially eligible articles [ 12 16 , 18 , 22 24 ]. After reviewing the full article, we found that three of them were based on one trial [ 13 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the remaining articles, 58 articles were excluded based on titles and abstracts, as the participants and interventions in these studies were irrelevant to the aim of this meta-analysis. Finally, the remaining 9 studies were potentially eligible articles [ 12 16 , 18 , 22 24 ]. After reviewing the full article, we found that three of them were based on one trial [ 13 , 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, two of them were excluded [ 22 , 23 ]. Two other articles were based on the same trial [ 15 , 24 ] and, again, one of them was rejected [ 24 ]. One article only compared the bioavailability of glucocorticoids between oral and intravenous administration but not clinical efficacy; therefore, we discarded this study as well [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…16 It demonstrated that there was no significant difference in the measured absorption of bioequivalent doses of oral prednisone vs. intravenous methylprednisolone. Two studies 7,26 suggested that no significant differences were found in peripheral blood T lymphocyte adhesion molecule expression, T cell subset distribution, TNFα concentrations or cytokine levels in patients of MS relapses whether treated with OMP or IVMP, providing further support to the concept that the two regimens are equivalent and their biological effect similar.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Therapeutic options to treat MS relapses include oral glucocorticosteroids [70,71] or their intravenous administration at a high dose as first line and therapeutic plasma exchange (TPE) and intravenous immunoglobulin (IVIG) as second line treatments in glucocorticosteroids unresponsive patients [72], corticotrophin injection and Acthar [73].…”
Section: Treatment Of Relapsesmentioning
confidence: 99%